Neurotensin, a Novel Messenger to Cross-Link Inflammation and Tumor Invasion via Epithelial-Mesenchymal Transition Pathway. (3rd July 2016) - Ye, Yingnan; Liu, Pengpeng; Wang, Yue; Li, Hui; Wei, Feng; Cheng, Yanan; Han, Lei; Yu, Jinpu
Abstract : Multiple cytokines and growth factors are critical for the prognosis of cancer which has been regarded as a worldwide health problem. Recently, neuropeptides, soluble factors regulating a series of functions in the central nervous system, have also been demonstrated to stimulate the proliferation and migration of tumor cells. Among these signaling peptides, the role of neurotensin (NTS) on malignancy procession has become a hot topic. The effects of NTS on tumor growth and its antiapoptosis role have already been identified. Subsequently, studies demonstrated the impact of NTS on the migration and invasion, but the molecular mechanisms involved are still unclear at present. Recently, some reports indicated that NTS could induce expression and secretion of interleukin-8 (IL-8) to promote local imflammatory response which might participate in epithelial-mesenchymal transition (EMT)-related tumor migration. In present review, we highlight the process of tumor EMT induced by NTS through stimulating IL-8 and the significance of NTS/IL-8 pathway in clinical application prospect.